Aspectos da biologia reprodutiva da arara-azul Anodorhynchus hyacinthinus (Latham, 1790) no mosaico Carajás-PA - Silva, Grace Ferreira da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Hyacinth macaw (Anodorhynchus hyacinthinus) is the biggest macaw in the world. This species is distributed in three regions of Brazil with apparently isolated populations. It is necessary that long-term studies about the reproductive biology and diet of macaws are made, since many of the important questions about the parrot ecology involve studies of their habitat and behavior. The objective of this research was to collect information about the aspects of the reproductive biology of Hyacinth macaws in the Carajás Mosaic region and its surroundings, as well as observing the food items they consume and thus increase knowledge about the species throughout its hit area of occurrence to assist the appropriate conservancy of the macaw. For four non-consecutive years, tree cavities were located and when active with eggs and / or chicks, the trees were registered as nest. We made observations and collect food items of the species. We obtained a total of 67 records cavities between the years 2007, 2008, 2013 and 2014. Twenty-four nests were active with eggs and chicks. We obtained a total of 67 records cavities where 24 were active with eggs and chicks. Most nest cavities were recorded in Sterculia sp. (87%) and the others in the plant species: Euxylophora paraensis, Bertholletia excelsa, Cariniana sp., Parkia sp., Ceiba pentandra, Bagassa guianensis, Parkia aff. Gigantocarpa, Helicostylis tomenosa, Schizolobium sp. During the breeding period, we observed that the hyacinth macaws occupy available hollows, without preference for the plant species. However, most of the nests were found in Sterculia sp. The laying of eggs followed as usual already observed in other populations of this psittacid species. Fruit remains of inajá palms (Maximiliana maripa), tucum (Astrocaryum sp.), Gueroba (Syagrus oleracea), macaúba (Acrocomia aculeata) and bacuri (Scheelea phalerata) were collected inside the nests, on the ground below the nest and next to the ...

A arara-azul (Anodorhynchus hyacinthinus) é a maior arara do mundo. Esta espécie está distribuída em três regiões do Brasil com populações aparentemente isoladas. Estudos realizados a longo prazo, relacionados a biologia reprodutiva e levantamento dos itens alimentares das araras são necessários, uma vez que muitas das perguntas importantes sobre a ecologia de psitacídeos envolvem estudos de seu habitat e comportamento. Assim, o objetivo desta pesquisa foi coletar informações sobre os aspectos da biologia reprodutiva das araras-azuis na região do mosaico Carajás e seu entorno, bem como observar as espécies vegetais que utilizam para se alimentar e assim, ampliar o conhecimento sobre a espécie em toda a sua área de ocorrência e auxiliar os planos de manejo para a preservação da mesma. Durante quatro anos não consecutivos, itens alimentares foram coletados, cavidades arbóreas foram localizadas e, quando ativas com ovos e/ou filhotes, as árvores foram cadastradas como ninho. Foram obtidos um total de 67 registros de cavidades, onde 24 estavam ativos com ovos e filhotes. A maioria das cavidades-ninho foram registradas em Sterculia sp. (87%) as demais, nas espécies vegetais: Euxylophora paraensis, Bertholletia excelsa, Cariniana sp., Parkia sp., Ceiba pentandra, Bagassa guianensis, Parkia aff. Gigantocarpa, Helicostylis tomenosa, Schizolobium sp. Durante o período reprodutivo, foi observado que as araras-azuis ocupam cavidades disponíveis sem indícios de preferencia pela espécie vegetal. Entretanto, a maioria dos ninhos foram encontrados em Sterculia sp. A postura dos ovos seguiu conforme o usual já verificado em outras populações desta espécie de psitacídeo. Restos de frutos de palmeiras de inajá (Maximiliana maripa), tucum (Astrocaryum sp.), gueroba (Syagrus oleracea), macaúba (Acrocomia aculeata) e bacuri (Scheelea phalerata) foram coletados dentro dos ninhos, no chão abaixo do ninho e próximo as palmeiras,...
Keywords: Reprodução; Alimentos; Comportamento; Arara-azul - Comportamento; Food